Calf thymus DNA helicase F, a replication protein A copurifying enzyme. - Georgaki, A (1994)
A DNA helicase from calf thymus, called DNA helicase F, copurified with replication protein A through several steps of purification including DEAE-Sephacel, hydroxyapatite and single stranded DNA cellulose. It is finally separated from replication protein A on FPLC Mono Q where the DNA helicase elutes after replication protein A. Characterization of the DNA helicase F by affinity labeling with [alpha 32P]ATP indicated that the enzyme has a catalytic subunit of 72 kDa. Gel filtration experiments suggested that DNA helicase F can exist both in a monomeric and an oligomeric form. The enzyme unwinds DNA in the 5'-->3' direction in relation to the strand it binds. All eight deoxyribonucleoside- and ribonucleosidetriphosphates could serve as an energy source. Testing a variety of DNA/DNA substrates demonstrated that the DNA helicase F preferentially unwinds very short substrates and is slightly stimulated by a single stranded 3'-tail. However, replication protein A allowed the DNA helicase to unwind much longer DNA substrates of up to 400 bases, indicating that the copurification of replication protein A with the DNA helicase F might be of functional relevance.